miR-4780 Derived from N2-Like Neutrophil Exosome Aggravates Epithelial-Mesenchymal Transition and Angiogenesis in Colorectal Cancer - Liang Wang; Yuqiang Shan; Sixin Zheng; Jiangtao Li; Peng Cui (Hindawi Limited, 2023)
Despite significant advances in diagnostic methods and treatment strategies, the prognosis for patients with advanced colon cancer remains poor, and mortality rates are often high due to metastasis. Increasing evidence showed that it is of significant importance to investigate how the tumor microenvironment participates in the development of colorectal cancer (CRC). In this manuscript, neutrophils were sequentially stimulated with all-trans retinoic acid and transforming growth factor-β in turn to induce the neutrophil polarization. Differentially expressed miRNA in neutrophil exosomes have been sequenced by microarray profile, and the effect of N2-like neutrophil-derived exosomal miR-4780 on epithelial-mesenchymal transition (EMT) and angiogenesis was investigated. In our results, we found that neutrophils were enriched in CRC tumor tissue and that CD11b expression correlated with tumor site and serous membrane invasion. At the same time, we demonstrated that internalization of N2 exosomes exacerbated the viability, migration, and invasion of CRC cell lines and inhibited apoptosis. To further investigate the molecular mechanism, we analyzed the miRNA expression profile in the N2-like neutrophils, which led to the selection of hsa-miR-4780 for the subsequent experiment. The overexpression of miR-4780 from N2-like neutrophil-derived exosomes exacerbated EMT and angiogenesis. Moreover, miR-4780 can regulate its target gene SOX11 to effect EMT and angiogenesis in CRC cell lines. CRC with liver metastasis model also validated that aberrant expression of miR-4780 in N2-like neutrophil exosomes exacerbated tumor metastasis and development of tumor via EMT and angiogenesis. In conclusion, our current findings reveal an important mechanism by which mR-4780 from N2-like neutrophil exosomes exacerbates tumor metastasis and progression via EMT and angiogenesis.